The influence of service quality, brand equity, promotion, and perception of justice on customer trust of sharia pawnshop service users - Nurissyarifah; Rahayu Mardikaningsih; Anna Zakiyah Hastriana (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2024)
In contemporary Indonesia, Islamic pawnshops are experiencing widespread growth, offering a Sharia-compliant collateral-based lending system that provides financial assistance to individuals. These institutions provide various financial products, including pawning services for gold, collateralized goods, vehicles, and electronics. This study investigates the impact of service quality, brand equity, promotional activities, and perceptions of fairness on customer trust among users of Islamic pawnshop services. Specifically, it aims to determine the level of customer trust in Islamic pawnshop companies, considering the quality of service and the ease of transactions they offer. Employing a quantitative methodology, this research utilizes both primary and secondary data. The target population encompasses all customers of Islamic pawnshops in Surabaya, from whom a sample of 50 respondents participated by completing questionnaires. The collected demographic data reveals that the majority of respondents (34.10%) were over 20 years of age, indicating the inclusion of both adolescent and adult participants. Furthermore, a significant portion (45.8%) were actively employed. Regarding gender, the sample comprised 24.9% male and 26.1% female respondents. In terms of educational background, the respondents exhibited diversity, with 46.7% holding vocational, high school, or diploma qualifications.